Asymptomatic coronavirus disease 2019 (COVID-19) carriers: are they infectious? - Wong, Yen Shen; Muhamad, Dzawani; How, Soon Hin; Mohamed, Mohamed Sapian; Mohd Arif, Nasrah; Soh, Tze Vee; Mohd Hashim, Suzana; Abdullah, Norazmi (Science and Education Publishing, 2020)
Coronavirus disease 2019 (COVID-19) is highly contagious in symptomatic patients as it is thought to be transmitted through respiratory droplets. However, it is debatable whether asymptomatic COVID-19 patients are contagious due to lack of data. From 1st March to 15th April 2020, a total of 247 COVID-19 cases were admitted to Tengku Ampuan Afzan Hospital and 1010 close contacts were identified. We studied the epidemiological and clinical outcomes in asymptomatic subjects, as well as estimated the metrics of disease transmission between asymptomatic, symptomatic, and pneumonia subjects. From a total of 125 asymptomatic subjects, majority (n=116,92.8%) remained asymptomatic upon discharge. Only 9 (7.2%) subjects developed mild symptoms after admission. Seven subjects had abnormal chest radiograph suggestive of pneumonia, and 22 subjects (17.6%) were found to have mild liver impairment. None of the asymptomatic subjects required oxygen support, inotropic support or ICU care during admission. Fifteen second generation COVID-19 cases were found transmitted from the asymptomatic group, with an attack rate of 3.9%, which was statistically significantly lower compared to the symptomatic (7.6%) or pneumonia groups (25.7%, p<0.001). In conclusion, asymptomatic COVID-19 patients show excellent clinical outcome. They are infectious but had a lower transmission risk compared with symptomatic or pneumonia patients.